Designing a Framework to Determine Steel Price in Egypt - Abdelbary, Alaa; Moustafa Amin,; Aiman A. Ragab,; Mohamed A. Ragheb, (IJRDO - Journal of Business Management, 2021)
The current paper focuses on the areas of steel industry, exchange rates and interest rates in Egypt. It aims to develop a framework for the steel price in Egypt according to local changes in the exchange, inflation, and interest rates. The objectives of this study are to: investigate the factors affecting the steel market price in Egypt, identify the effect of competitive pressure from local and foreign steel players on steel market prices in Egypt, analyze the main elements that might affect the steel market price in Egypt, and develop a framework for the influencing factors to cope with the steel market price. Therefore, the problem the paper examines could be defined as the steel industry in Egypt should find a way to have its market share by competing with other participants in the global market. Thus, secondary data will be collected to describe the relationships assigned between the paper variables. The population is Egyptian steel companies while the sample used for this paper is Ezz steel company about each of the paper variables monthly from the year 2000 up to the year 2019. Such a study is important to develop a framework for the steel price in Egypt according to changes in the exchange rate, inflation rates, and interest rate in Egypt. The paper philosophy adopted in this paper is a Pragmatism Philosophy. The approach adopted in this paper includes the “Quantitative Approach” and the design adopted is the “Deduction Method”. The findings from this research provides evidence that ore iron price and scrap price have a positive significant impact on steel market price. The finding of analysis shows that there is a positive correlation between the natural gas prices, electricity prices, and steel market price. On the one hand, it is noticed after examination that there is a positive significant relationship between both the inflation rate and exchange rates on the steel market price. On the other hand, there is a negative significant relationship between interest rate and steel market price. This paper recommends that there is a need to focus on the macroeconomic terms and elements that may affect the level of price in the steel market; namely inflation, interest, and exchange rates. It should also recognize the rule of the raw materials (iron ore price and scrap price) in the process of pricing system of steel in Egypt. Finally, the Egyptian government should facilitate the sources of energy for the process of production to reduce the cost of production.